THE INFLUENCE OF CORPORATE GOVERNANCE STRUCTURE ON COMPANY TRANSPARENCY AND DISCLOSURE WHICH IS MODERATE BY MEDIA COVERAGE - Slin Slin; Ivone Ivone (Universitas Internasional Batam, 2024)
Transparency and disclosure are carried out by companies with the aim of increasing the company's image in the eyes of stakeholders and to reduce information asymmetry between companies and investors. Disclosure of relevant information helps eliminate the knowledge gap between executives and shareholders so as to reduce agency costs. This study aims to analyze the factors that influence independent commissioners, independent audit committees, gender diversity on transparency and company disclosure, which of course is moderated by coverage. media. These factors can affect the transparency and disclosure of the company. Public financial companies listed on the IDX from 2016 to 2020 are the sample studied, and a purposive sampling technique was used to select a sample of 88 companies. The study uses panel data regression techniques which mix time series and cross sectional. Outlier test, descriptive statistics, F and t test, and R2 test are some of the methods used. The random effect model (REM) is used as the basis for the analysis. The results of the research based on research model 1 prove that media coverage and gender diversity have a significant positive effect on company transparency and disclosure, but the independent board of commissioners has a significant negative effect on company transparency and disclosure, then the independent audit committee has no significant effect on company transparency and disclosure. The results of the research based on research model 2 prove that media coverage is able to strengthen the relationship between independent commissioners and corporate transparency and disclosure. But media coverage weakens the link between independent audit committees and gender diversity and corporate transparency and disclosure